'Regionalism' and the global trade system. (16th June 2021) - Pomfret, Richard
Abstract: The post‐1945 global trading system was designed around the principle of non‐discrimination. During the 1947–94 GATT era, regionalism and multilateralism were often viewed as antagonistic approaches to international trade, and preferential treatment within regional blocs was to be deterred. Since 1995, although regional trade agreements are monitored by the WTO Secretariat and presented as a threat to the system, regionalism poses little threat to the multilateral trading system. This paper argues that major twenty‐first century RTAs go beyond preferential tariff treatment to focus on deeper integration issues. Such issues are addressed outside the WTO because, despite new features of the international trade map since 1995 such as Internet use and global value chains, extension of WTO rules has proved difficult due to the requirement for consensus. The paper analyses the rise of megaregional agreements such as CPTPP and RCEP, the shift in EU policy from protecting domestic producers to facilitating imports from best global suppliers and the use of WTO plurilateral agreements within the context of providing rules fit for purpose in the modern global trading system.